Is ESSA a retreat from equity?. (October 2019) - Fusarelli, Lance D.; Ayscue, Jennifer B.
The passage of ESSA has ushered in a new era of educational governance and leadership, but questions remain regarding how well the new law will protect students' rights to an equitable education. Lance Fusarelli and Jennifer Ayscue examine key provisions of the law, provide an update of states' implementation, and speculate about whether ESSA will encourage states to create policies to reduce disparities or whether the return to state and local control will further exacerbate inequities. They encourage educators and policy makers to pay close attention to what is happening in their states and share examples of how states are and are not making equity part of their ESSA plans .